A Review of Complementary and Alternative Treatments for Autism Spectrum Disorders. (28th November 2012) - Lofthouse, Nicholas; Hendren, Robert; Hurt, Elizabeth; Arnold, L. Eugene; Butter, Eric
Abstract : Given the severe and chronic problems associated with Autism Spectrum Disorders (ASD) and the limitations of available treatments, there exists a large public health need for additional interventions. As more parents are inquiring about complementary and alternative treatments (CATs), both parents and practitioners require up-to-date information about them and whether and how to integrate them into treatment. After presenting data on CAT usage patterns for ASD, we review 13 ingestible (i.e., orally administered) and 6 noningestible (i.e., externally administered) CATs for ASD. For each CAT we briefly describe its definition; rationale for use; current research support, limitations, and future directions; safety issues; and whether we currently recommend, not recommend, or find it acceptable for the treatment of ASD. We conclude this paper with recommendations for future research and ten clinical recommendations for practitioners.